Myricetin suppresses TGF-β-induced epithelial-to-mesenchymal transition in ovarian cancer - Yang, Hui-Wen; Lan, Yan; Li, An; Wu, Han; Song, Zi-Wei; Wan, Ai-Ling; Wang, Yue; Li, Shi-Bao; Ji, Shuai; Wang, Zhong-Cheng; Wu, Xin-Yu; Lan, Ting (Frontiers in Pharmacology, 2023)
Background: Ovarian cancer (OC) is the second most common gynecological malignancy and has a high mortality rate. The current chemotherapeutic drugs have the disadvantages of drug resistance and side effects. Myricetin, a kind of natural compound, has the advantages of easy extraction, low price, and fewer side effects. Multiple studies have demonstrated the anti-cancer properties of myricetin. However, its impact on OC is still unknown and needs further investigation. Therefore, this study aimed to elucidate the mechanism by which myricetin suppresses transforming growth factor-β (TGF-β) -induced epithelial-to-mesenchymal transition (EMT) in OC through in vivo and in vitro experiments. Method: In vitro experiments were conducted to evaluate the effects of myricetin on cell proliferation and apoptosis using CCK8 assay, plate clonal formation assay, and flow cytometry. Western blot was employed to evaluate the expression levels of caspase-3, PARP, and the MAPK/ERK and PI3K/AKT signaling pathways. Wound healing, transwell, western blot and immunofluorescence assay were used to detect TGF-β-induced cell migration, invasion, EMT and the levels of Smad3, MAPK/ERK, PI3K/AKT signaling pathways. Additionally, a mouse xenograft model was established to verify the effects of myricetin on OC in vivo. Results: Myricetin inhibited OC proliferation through MAPK/ERK and PI3K/AKT signaling pathways. Flow cytometry and western blot analyses demonstrated that myricetin promoted apoptosis by increasing the expression of cleaved-PARP and cleaved-caspase-3 and the ratio of Bax/Bcl-2 in OC. Furthermore, myricetin suppressed the TGF-β-induced migration and invasion by transwell and wound healing assays. This is a provisional file, not the final typeset article Mechanistically, western blot indicated that myricetin reversed TGF-β-induced metastasis through Smad3, MAPK/ERK and PI3K/AKT signaling pathway. In vivo, myricetin significantly repressed OC progression and liver and lung metastasis. Conclusion: Myricetin exhibited inhibitory effects on OC progression and metastasis both in vivo and in vitro. And it also reversed TGF-β-induced EMT through the classical and non-classical Smad signaling pathways.